A straightforward molecular strategy to retrospectively investigate the spread of SARS-CoV-2 VOC202012/01 B.1.1.7 variant - Gabriele Ibba; Rosangela Sau; Flavia Angioj; Marcello Abbondio; Salvatore Rubino; Sergio Uzzau (Journal of Infection in Developing Countries)
The spread of new SARS-CoV-2 variants represents a serious threat worldwide, thus rapid and cost-effective methods are required for their identification. Since November 2020, the TaqPath COVID-19 assay (Thermo Fisher Scientific) has been used to identify viral strains of the new lineage B.1.1.7, since it fails to detect the S-gene with the ∆69/70 deletion. Here, we proposed S-gene mutations screening with the Allplex SARS-CoV-2 assay (Seegene), another widely used RT-PCR test that targets Sarbecovirus E, SARS-CoV-2 N, and RdRp/S genes. Accordingly, we evaluated the S gene amplification curve pattern compared to those of the other genes. Exploiting an Allplex assay-generated dataset, we screened 663 RT-PCR digital records, including all SARS-CoV-2 respiratory samples tested in our laboratory with the Allplex assay between January 1st and February 25th, 2021. This approach enabled us to detect 64 samples with peculiar non-sigmoidal amplification curves. Sequencing a selected group of 4 RNA viral genomes demonstrated that those curves were associated with B.1.1.7 variant strains. Our results strongly suggest that B.1.1.7 variant spread has begun in this area at least since January and imply the potential of these analytical methods to track and characterize the spread of B.1.1.7 strains in those areas where Allplex SARS-CoV-2 datasets have been previously recorded.